Seminar on Stochastic Analysis, Random Fields and Applications V Centro Stefano Franscini, Ascona, May 2005 - Dalang, Robert; Dozzi, Marco; Russo, Francesco (Progress in Probability, 2008)
This volume contains twenty-eight refereed research or review papers presented at the 5th Seminar on Stochastic Processes, Random Fields and Applications, which took place at the Centro Stefano Franscini (Monte Verità) in Ascona, Switzerland, from May 30 to June 3, 2005. The seminar focused mainly on stochastic partial differential equations, random dynamical systems, infinite-dimensional analysis, approximation problems, and financial engineering. The book will be a valuable resource for researchers in stochastic analysis and professionals interested in stochastic methods in finance. Contributors: Y. Asai, J.-P. Aubin, C. Becker, M. Benaïm, H. Bessaih, S. Biagini, S. Bonaccorsi, N. Bouleau, N. Champagnat, G. Da Prato, R. Ferrière, F. Flandoli, P. Guasoni, V.B. Hallulli, D. Khoshnevisan, T. Komorowski, R. Léandre, P. Lescot, H. Lisei, J.A. López-Mimbela, V. Mandrekar, S. Méléard, A. Millet, H. Nagai, A.D. Neate, V. Orlovius, M. Pratelli, N. Privault, O. Raimond, M. Röckner, B. Rüdiger, W.J. Runggaldier, P. Saint-Pierre, M. Sanz-Solé, M. Scheutzow, A. Soós, W. Stannat, A. Truman, T. Vargiolu, A.E.P. Villa, A.B. Vizcarra, F.G. Viens, J.-C. Zambrini, B. Zegarlinski.